Istanbul: A Global, but Still Industrial, City - Özgür Sayın (Journal of Economy Culture and Society)
Global cities are typically perceived as the outcomes of a series of structural transformations experienced by the advanced capitalist countries in North America and Western Europe in the 1970s. A radical decrease in the share of industrial production vis-à-vis an increase in advanced producer services in the sectorial composition of global cities is one of the indicators of such restructuring. However, beyond the North Atlantic Axis—and especially with regard to new global cities the validity of this assumption is questionable. Consequently, this paper involves a case study of Istanbul on the subject. This paper considers economic production and employment levels as well as spatial indicators to explore the changes in the sectorial dynamics of Istanbul's economy following the 2000s. Furthermore, it evaluates whether post-industrial transformation has taken place in the city. The first empirical section of the paper argues that such post-industrial transformation has not taken place in Istanbul; it posits that rather, globalization has spurred some changes in the manufacturing industry in terms of the scale of production and spatial distribution within the city. It further discusses the local and global dynamics contributing to the survival of industries in the city.